THEORETICAL ASPECTS OF STUDYING THE SOCIO-MORAL ATTITUDES OF THE THINKERS OF THE TEMURIAN PERIOD (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical-methodological foundations of researching the socio-ethical views of the thinkers of the Timurid era, the hermeneutic bases of their socio-ethical views, the educational significance of the socio-ethical views of the thinkers of the Timurid era in New Uzbekistan are studied. Theoretical aspects of studying the socio-moral attitudes of the thinkers of the Temurian period was also analyzed.